Pengaruh Metaverse Dalam Meningkatkan Motivasi Dan Keterlibatan Siswa Dalam Proses Pembelajaran - Abidin, Rusman Zaenal; Ruhiat, Yayat; Nurhakim, Lukman (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
The concept of the metaverse, integrating virtual and augmented realities, has emerged as a promising innovation in educational technology to enhance student motivation and engagement. This study systematically reviews the impact of metaverse-based environments on the learning process, focusing on how its elements such as gamification and immersive experiences foster interactive and effective learning. By bridging traditional and modern educational methods, the metaverse creates realistic simulations and dynamic collaboration opportunities, fulfilling students' psychological needs for autonomy, competence, and connectedness. Results indicate significant improvements in motivation, participation, and academic outcomes when using metaverse platforms. Furthermore, the research emphasizes the importance of technological readiness and adaptive teaching strategies to optimize metaverse applications. These findings suggest that integrating the metaverse into education can transform learning experiences, making them more engaging and aligned with the needs of a digitally native generation.